2014
DOI: 10.1124/dmd.114.058305
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Assessing Potential Drug-Drug Interactions of a Concomitant Agent against a Drug Absorbed via an Intestinal Transporter in Humans

Abstract: A strategy for assessing potential drug-drug interactions (DDIs) based on a simulated intestinal concentration is described. The proposed prediction method was applied to the DDI assessment of luseogliflozin, a novel antidiabetic drug, against miglitol absorbed via the intestinal sodium-glucose cotransporter 1 (SGLT1). The method involves four steps: collection of physicochemical and pharmacokinetic parameters of luseogliflozin for use in a computer simulation; evaluation of the validity of these parameters by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…A large number of literature studies were investigated to obtain the data for (i) model development: ① physicochemical and biochemical properties of LUS; , ② binding kinetics; ③ affinity to SGLTs for glucose and expression of SGLT data; and ④ physiological parameters for renal tubules . The data have been summarized in Table .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of literature studies were investigated to obtain the data for (i) model development: ① physicochemical and biochemical properties of LUS; , ② binding kinetics; ③ affinity to SGLTs for glucose and expression of SGLT data; and ④ physiological parameters for renal tubules . The data have been summarized in Table .…”
Section: Methodsmentioning
confidence: 99%
“… 19 The data have been summarized in Table 1 . (ii) Model validation: ① PK validation: clinical PK concertation–time profiles 12 , 21 , 23 , 24 and ② UGE validation: clinical cumulative UGE–time and UGE rate–time profiles. 23 , 24 …”
Section: Methodsmentioning
confidence: 99%
“…Because even selective SGLT2 inhibitors have an inhibitory effect on SGLT1 and the intestinal concentration of such inhibitors can be much higher than the IC 50 value for SGLT1, we assessed the clinical DDI potential of luseogliflozin against miglitol. Based on the simulated intestinal concentration and the rapid absorption of luseogliflozin, the potential DDI was estimated to be low (Mizuno-Yasuhira et al, 2011). Actually, luseogliflozin reportedly has no clinically relevant effect on the pharmacokinetics of miglitol (Sasaki et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that miglitol, a synthetic N-hydroxyethyl derivative of DNJ, was absorbed into the bloodstream by a sugar transporter, namely, sodium-glucose cotransporter 1 (SGLT1). 8 Based on this finding, we hypothesized that sugar transporters, such as the sodium-glucose cotransporter (SGLT) or the glucose transporter (GLUT) might facilitate the intestinal absorption and organ uptake of other types of aza-sugars. In the second part of our study, we investigated this in vivo (Experiment 2) and in vitro (Experiment 3) using acknowledged inhibitors of sugar transporters.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding this information is critical to gain more insight into the action mechanism and safety of aza-sugars once ingested. It was reported that miglitol, a synthetic N -hydroxyethyl derivative of DNJ, was absorbed into the bloodstream by a sugar transporter, namely, sodium-glucose cotransporter 1 (SGLT1) . Based on this finding, we hypothesized that sugar transporters, such as the sodium-glucose cotransporter (SGLT) or the glucose transporter (GLUT) might facilitate the intestinal absorption and organ uptake of other types of aza-sugars.…”
Section: Introductionmentioning
confidence: 99%